Political, social and cultural integration of the immigrants from India in the United States of America - Rezková, Hana; Dvořáková, Vladimíra, 1957-; Chalupský, Rudolf; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
This paper deals with the political, social and cultural integration of the immigrants from India in the United States of America. The last and so far the biggest wave of Asian Indian immigration to the U.S. began after 1965 with the passage of the new Immigration Act. Today, there are more than 2.5 million Asian Indian immigrants living in the U.S. The aim of this thesis is to analyze the chronology of events and history of U.S. immigration laws concerning Asian, and particularly Asian Indian, immigrants. Building on this analysis, the goal is further to show how the immigrants were being discriminated against and how they managed to integrate successfully into the mainstream American society despite many cases of refusal and acts based on prejudice. The Social Integration part analyzes possible problems in the Asian Indian immigrant family living in the U.S., their attitudes towards education, and finally their success at work. The Cultural Integration part includes the topic of multiculturalism, issues of conflict and communication, differences between the American and Indian culture, as well as religion, holidays, and traditions.
Vedoucí práce: Vladimíra Dvořáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2009
Rok obhajoby 2009
Keywords: mezinárodní a evropská studia - diplomacie [obor dipl. práce]; diplomové práce; master's theses